Continuing professional development of lecturer’s research training model based on research product - Aan Komariah, Asep Suryana, Junihot M. Simanjuntak, Udin Syaefuddin Sa'ud, (Opción, 2019)
This research specifically talks about the continuitydevelopment in the university through training model based onresearch product and publication of scientific work that support theuniversity quality enhancement via qualitative methods with Researchand Development (R&D) model approaches. As a result, the ongoingtraining has not been done programmatically and has not been able tomake lecturers learn independently. In conclusion, product basedtraining model development IS done through these steps: (a) analysis;(b) planning; (c) development; (d) implementation; (e) evaluation.